1996
DOI: 10.1111/j.1574-6968.1996.tb07989.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a genus specific primer set for detection ofLeishmaniaparasites by polymerase chain reaction

Abstract: We have compared the sequences of a major class of kinetoplast DNA (kDNA) minicircle (pLURkE3) of Leishmania strain UR6 with other minicircle sequences from different Leishmania species. Alignment of these sequences allowed the selection of a pair of oligonucleotides suitable as primers in polymerase chain reaction (PCR) which is specific for Leishmania parasites. PCR with this genus-specific primer set is capable of detecting 1 femtogram of kDNA. These primers have been tested with kDNAs from both old world a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In addition, diagnostic studies have gained momentum. The diagnosis of leishmaniasis has been approved by isolating, visualizing, and culturing the parasite from infected tissue, historically [104]. It explains that there is a serious need to develop more expensive, precise, sensitive, rapid, and specific diagnostic tests, especially for the detection of leishmaniasis [105].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diagnostic studies have gained momentum. The diagnosis of leishmaniasis has been approved by isolating, visualizing, and culturing the parasite from infected tissue, historically [104]. It explains that there is a serious need to develop more expensive, precise, sensitive, rapid, and specific diagnostic tests, especially for the detection of leishmaniasis [105].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we tried to detect Leishmania species using several PCR assays and compared the sensitivity and specificity of these methods. Generally, the use of highly repetitive genomic loci or extrachromosomal kDNA sequences is the most common method, which is confined to the detection of parasites at the genus or complex levels ( 18 ). The present study showed that, while PCR based on minicircle kDNA sequences could correctly detect the positive samples, it is not a good tool to differentiate and identify the Leishmania isolates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, bile exposure in E. coli increases expression of multidrug-efflux pumps including AcrAB and EmrAB that promote bile tolerance and increase antibiotic efflux [35, 36]. In S. typhimurium , an AcrB-like protein that encodes for an efflux pump contributes to resistance to both bile salts and detergents [37, 38]. Bile exposure in Enterococcus faecalis induces genes encoding for EmrB/QacA family drug resistance transporters and increases expression of phospholipid synthetase which is linked to daptomycin resistance [39].…”
Section: Introductionmentioning
confidence: 99%